Effects of autonomic nervous system disorders on male infertility - Qiu, Qixiang; Chen, Jincong; Xu, Nengquan; Zhou, Xiaolong; Ye, Chenlian; Liu, Min; Liu, Zhaoxia (Frontiers in Neurology, 2023)
The male reproductive functions are largely regulated by the autonomic nervous system. Male sexual behavior and fertility primarily depend on the normal function of the higher neural centers related to the autonomic nervous system, the hypothalamic–pituitary–gonadal axis, the autonomic nervous components within the spinal cord and spinal nerves, and certain somatic nerves in the pelvic floor. In this review article, we will summarize the role of the autonomic nervous system in regulating male reproductive capabilities and fertility, its impact on male infertility under abnormal conditions, including the role of drug-induced autonomic nervous dysfunctions on male infertility. The main purpose of this article was to provide an overview of the effects of autonomic nervous dysfunction on male reproductive function and shed light on the potential therapeutic target for male infertility.